FBP1 knockdown decreases ovarian cancer formation and cisplatin resistance through EZH2-mediated H3K27me3. Issue 9 (30th September 2022) - Xiong, Xifeng; Lai, Xudong; Zhang, Jinli; Meng, Qingqi; Wang, Pengzhen; Qin, Shengnan; Liu, Wei; Wang, Yongxuan; Yao, Zhuo; Wang, Di; Li, Xiaojian; Liu, Zhihe; et al.
Abstract: Worldwide, ovarian cancer (OC) is the seventh common cancer and the second most common cause of cancer death in women. Due to high rates of relapse, there is an urgent need for the identification of new targets for OC treatment. The far-upstream element binding protein 1 (FBP1) and enhancer of zeste homolog 2 (EZH2) are emerging proto-oncogenes that regulate cell proliferation and metastasis. In the present study, Oncomine data analysis demonstrated that FBP1 was closely associated with the development of OC, and The Cancer Genome Atlas (TCGA) data analysis indicated that there was a positive correlation between FBP1 and EZH2 in ovarian tissues. Moreover, we found that FBP1 knockdown suppressed tumor formation in nude mice and cisplatin resistance of OC cells, but the role of FBP1 in the cisplatin resistance of OC cells remained unclear. In addition, we verified physical binding between FBP1 and EZH2 in OC cells, and we demonstrated that FBP1 knockdown enhanced cisplatin cytotoxicity in OC cells and down-regulated EZH2 expression and trimethylation of H3K27. These results suggested that FBP1 increases cisplatin resistance of OC cells by up-regulating EZH2/H3K27me3. Thus, FBP1 is a prospective novel target for the development of OC treatment.